Manna-X : um framework para Ambientes inteligentes - Couto, Guilherme Simão (2012)
In the development of Intelligent Environments (IE) solutions different technologies can be used since they offer comfort and transparency to the users. The diversity of devices and technologies must follow a major requirement, invisibility, i.e. the inhabitants of the environment should not be aware that the technology is embedded and performing tasks with different objectives, e.g. to provide welfare to the inhabitants, cooperate to sustainability, monitoring entities (people, animals and things), among others. The elements of IE will be exchanging information, collaborating and cooperating with each other and with the user in achieving the goals defined for the environment. This leads to a heterogeneous environment which requires a way to provide exchanges between elements from different technologies. The task of integrating diversity is not trivial. This thesis deals with this challenge: to study the concepts related to Intelligent Environments, identify research opportunities and propose a solution for the integration of different technologies. In particular, the thesis we propose a framework called Manna-X and develop prototypes as proof of concepts of good practice set to assist developers and manufacturers in the intelligent environments implementation. In this work the following areas and technologies are involved: Wireless Sensor Networks, Internet of Things, Kinect, Zigbee, among others.